Spatiotemporal Distributions of Sheep and Goat Pox Disease Outbreaks in the Period 2013–2019 in Eastern Amhara Region, Ethiopia - Sileshi Aregahagn; Belege Tadesse; Bethelihem Tegegne; Yalelet Worku; Seid Mohammed (Veterinary Medicine International)
Sheep and goat pox is highly contagious viral infection of sheep and goats caused by the genus Capripox virus. Clinically, the disease is characterized by fever, macules developing into papules, and necrotic lesions in the skin and nodular lesions in internal organs. In Ethiopia, there are seroprevalence epidemiological studies on the disease. However, the spatiotemporal clustering of sheep and goat pox incidence has not been investigated. A retrospective study design using the outbreak reported data from Kombolcha Regional Laboratory for the years from September 2013 to December 2019 was performed to determine the temporal and spatial distribution of sheep and goat pox outbreaks. A total of 663 sheep and goat pox disease outbreaks were reported in all major parts of Eastern Amhara region between 2013 and 2019. In this period, sheep and goat pox was reported in all administrative zones of Eastern Amhara region (n = 5). The average incidence of sheep and goat pox outbreaks at the district level was 8.61 per 7 years. The incidence differed between areas, being the lowest in hot dry month and highest in warm and cold moist months. Sheep and goat pox outbreaks generally have a peak in November followed by August and a low in May. There is a significant difference in the occurrence of sheep and goat pox disease outbreaks between months and years (p<0.001). The forecast for the period 2020–2026 revealed that a high number of sheep and goat pox disease outbreaks will occur than the previous one. Therefore, all stakeholders should work cooperatively to combat this disease occurrence, and there should be capacity development for participatory disease search, risk analysis, laboratory diagnosis, and information management in order to respond properly to outbreak of sheep and goat pox disease; thereby, it enhances the prevention and control the disease.